The Use of Artificial Neural Network (ANN) for Modelling, Simulation and Prediction of Advanced Oxidation Process Performance in Recalcitrant Wastewater Treatment - Elmolla, Emad S.; Chaudhuri, Malay (IntechOpen, 2011)
None